Employee Performance with a Motivation as Intervening Variable: The Case of Private Hospitals in Palembang, Indonesia - Saleh, Rahmat; Rahayu, Sri; Yamaly, Fadhil (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study aims to determine the effect of work discipline and work environment on employee performance with work motivation as an intervening variable at Swasta Hospital in Palembang. This type of research is associative. The variables researchers use are work discipline, work environment, work motivation, and performance. The sample in this study was 180 employees of Muhammadiyah Hospital in Palembang selected by cluster sampling. The data used in this study is primary data with a questionnaire data collection method. The data analysis technique used is Structural Modeling Equation (SEM) with the Lisrel Program Application. The results of this study indicate that (1) work discipline has a positive and significant effect on work motivation, (2) work environment has a positive and significant effect on work motivation, (3) work discipline has a positive and significant effect on employee performance, (4) work environment has a positive and significant effect on employee performance, (5) work motivation has a positive and significant effect on employee performance at Muhammadiyah Hospital in Palembang